Experimental, DFT and molecular dynamic simulation of Andrographis paniculata as corrosion inhibitor for mild steel in artificial seawater - Kamaruzzaman W.M.I.W.M.; Shaifudin M.S.; Nasir N.A.M.; Badruddin M.A.; Yusof N.; Adnan A.; Aziz N.A.; Nik W.M.N.W.; Haque J.; Murmu M.; Banerjee P.; Mohd Ghazali M.S. (My University, 2025)
At present, one of the crucial goals in the field of corrosion control practices is to develop sustainable, non-degradable and eco-friendly corrosion inhibitors. Herein, Andrographis paniculata essential oil developed from the leaf part was investigated as an excellent corrosion inhibitor to prevent or reduce corrosion on the surface of mild steel when exposed to artificial seawater. Several characterizations were used to examine the efficacy of the materials, including the classical weight loss study, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) coupled to an energy dispersive X-ray (EDX), field emission scanning electron microscopy (FESEM), density functional theory (DFT), molecular dynamic (MD) simulation and antimicrobial assessment using the disk-diffusion method. The findings indicate that the inhibitors act as mixed-type inhibitors that follow the Langmuir adsorption isotherm. Furthermore, the corrosion inhibition potential of major compounds present in the inhibitor was also geometrically optimized and calculated. Last but not least, through the antimicrobial test against 6 bacteria, the extract achieved excellent results against all bacteria, with the highest efficiency recorded at 65.10 % against Pseudomonas aeruginosa. © 2023 Elsevier B.V.